Monitoring compliance to an experimental treatment in an asymptomatic population - Durval Rosa Borges (Einstein (São Paulo), 2008)
Objective: To develop strategies and to monitor patient’s adherence to the follow up of the experimental treatment of secondary cholestasis in its isolate chronic form with portal hypertension. Methods: Experimental study made with 11 patients. Ursodeoxycholic acid was administered in the dosage of 15 mg/kg/day twice a day for 45 days. Evaluation of adherence was performed using pill count strategy and interviews. Rresults: The variation during pill count had no influence on the patient’s laboratory results. Serum activity of γGT normalized during treatment, returning to increased levels after interruption of medication. Cconclusions: The strategies developed were effective presenting a significant laboratory result regarding the decrease of γGT serum activity.